Moral Exceptionalism and the Just War Tradition: Walzer’s Instrumentalist Approach and an Institutionalist Response to McMahan’s “Nazi Military” Problem - Ford, Shannon (2022)
The conventional view of Just War thinking holds that militaries operate under “special” moral rules in war. Conventional Just War thinking establishes a principled approach to such moral exceptionalism in order to prevent arbitrary or capricious uses of military force. It relies on the notion that soldiers are instruments of the state, which is a view that has been critiqued by the Revisionist movement. The Revisionist critique rightly puts greater emphasis on the moral agency of individual soldiers: they are not mere instruments of the state. Although Revisionism has something particularly important to contribute when applied to cases that are short-of-war, where an individual agent’s moral culpability plays a greater role, soldiers fighting wars are not wholly autonomous moral agents. An Institutionalist approach that responds to Revisionist criticisms is a plausible alternative to the conventional Just War account for grounding the moral exceptionalism of war. For the Institutionalist, soldiers are moral agents with state-imposed obligations whose fundamental responsibility is the performance of the proper moral ends of the military institution they serve. If this is true, then soldiers have a moral obligation to be attentive to the moral corruption of the military institution of which they are a part.